"Bersenang-senang dalam keberlanjutan": Konsep hedonistic sustainability pada karya Bjarke Ingels - Nita Dwi Estika; Yudhistira Kusuma; Dewi Retno Prameswari; Iwan Sudradjat (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Contemporary architects highlight past ideas and present new manifestos often perceived as utopian. Bjarke Ingels introduced hedonistic sustainability in response to the demand for environmentally friendly and sustainable living through different perspectives. This paper comprehensively explains the concept of hedonistic sustainability through the designs of Bjarke Ingels, a contemporary architect. Literature from various sources is examined to describe Bjarke Ingels' idea. Hedonistic sustainability combines sustainable ideas, fun, and community. Bjarke Ingels's architectural design is applied through simulation and an ironic approach. Its representation facilitates the exploration of the design objects planned concretely. The idea of playful and communality was raised through the design that accommodates various user activities. Bjarke Ingels's idea is expected to contribute to the knowledge and contemporary architecture design process in Indonesia. © 2020 Nita Dwi Estika, Yudhistira Kusuma, Dewi Retno Prameswari, Iwan Sudradjat